Quantifying antiepileptic drug effects using intrinsic excitability measures. (26th August 2016) - Meisel, Christian; Plenz, Dietmar; Schulze‐Bonhage, Andreas; Reichmann, Heinz
Summary: Pathologic increases in excitability levels of cortical tissue commonly underlie the initiation and spread of seizure activity in patients with epilepsy. By reducing the excitability levels in neural tissue, antiepileptic drug (AED) pharmacotherapy aims to reduce seizure severity and frequency. However, AEDs may also bring about adverse effects, which have been reported to increase with higher AED load. Measures that monitor the dose‐dependent effects of AEDs on cortical tissue and quantify its excitability level are therefore of prime importance for efficient clinical care and treatment but have been difficult to identify. Here, we systematically analyze continuous multiday electrocorticography (ECoG) data from 10 patients under different levels of AED load and derive the recently proposed intrinsic excitability measures (IEMs) from different brain regions and across different frequency bands. We find that IEMs are significantly negatively correlated with AED load (prescribed daily dose/defined daily dose). Furthermore, we demonstrate that IEMs derived from different brain regions can robustly capture global changes in the degree of excitability. These results provide a step toward the ultimate goal of developing a reliable quantitative measure of central physiologic effects of AEDs in patients with epilepsy.